2010
DOI: 10.1038/embor.2010.113
|View full text |Cite
|
Sign up to set email alerts
|

Histone Sin mutations promote nucleosome traversal and histone displacement by RNA polymerase II

Abstract: Nucleosome traversal by RNA polymerase II (pol II) and recovery of chromatin structure after transcription are essential for proper gene expression. In this paper we show that nucleosomes assembled with Sin mutant histones present a much weaker barrier to traversal by pol II and are less likely to survive transcription. Increases in traversal from incorporation of Sin mutant histones and histones lacking H2A/H2B amino-terminal tails were in most cases additive, indicating that traversal can be facilitated by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 15 publications
4
63
1
Order By: Relevance
“…Although facilitating unfolding of critical histone-DNA contacts clearly improves transcription through nucleosomes by pol II, traversal in the in vitro studies just cited remained incomplete and slow relative to transcription of pure DNA templates (21,23 template when it encounters transcriptional barriers, including arrest sites on pure DNA templates (24,25) and nucleosomes (17). Thus, effective nucleosome traversal is likely to require factors that hold pol II in the transcriptionally competent configuration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although facilitating unfolding of critical histone-DNA contacts clearly improves transcription through nucleosomes by pol II, traversal in the in vitro studies just cited remained incomplete and slow relative to transcription of pure DNA templates (21,23 template when it encounters transcriptional barriers, including arrest sites on pure DNA templates (24,25) and nucleosomes (17). Thus, effective nucleosome traversal is likely to require factors that hold pol II in the transcriptionally competent configuration.…”
mentioning
confidence: 99%
“…These contacts are specifically disrupted by point mutations in histone H3 or H4 called Sin mutants (20). We have recently shown that nucleosomes containing Sin mutant histones do provide a significantly lower barrier to nucleosome traversal by pol II (21). Single-nucleosome unfolding studies have demonstrated that removal of the N-terminal tail domains from histones H2A and H2B specifically favors DNA unwrapping 45-55 bp within the nucleosome (22).…”
mentioning
confidence: 99%
“…They found that for almost all genes, the first nucleosome is a major barrier for the elongation. This fact has been also observed in vitro by other people [1], [2] and mathematical model based on these in vitro results are also introduced [4]. However, in vivo studies show barrier positions that differ from in vitro results [3].…”
Section: Introductionmentioning
confidence: 84%
“…We use a computer code (See supplementary materials) to find these optimal μ in [0.01,0.6] and σ in [1,60] for nucleosomes on different genes (e. g.μ 1 and σ 1 for all +1 nucleosomes, μ 2 and σ 2 for all +2 nucleosomes, and so on). We employ magnitude (M) as another degree of freedom which is unique for any individual nucleosome.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation